The cultural and economic context of maternal infantcide : a crying baby and the inability to escape - Smithey, Martha (Emerald Publishing Limited, 2019)
This book examines the social, economic and cultural conditions and stressors under which mothers commit infanticide, and shows how these conditions affect the ability to meet societal and self-perceived expectations of ""good"" mothering.
Keywords: Infanticide.; Motherhood -- Social aspects.; Motherhood -- Cross-cultural studies.; Motherhood -- Psychological aspects.; Motherhood.; elektronické knihy; Cross-cultural studies.; electronic books